WOMEN ISSUES IN HILLARY CLINTON’S SPEECHES - Elsa Emiria Leba (Rubikon : Journal of Transnational American Studies, 2015)
Women’s rights to contribute freely in many life spheres are now granted by law. Yet, Hillary Clinton as a U.S. prominent politician still discusses about women’s issues in her speeches. This article discusses about Hillary’s views, types, and solutions of women’s issues that are found in her political speeches from the year 2007 until 2013.This research is conducted under American Studies applying an interdisciplinary approach, which uses anthropology, sociology, and historical-biographical disciplines, as well as reconciliation of tenses approach that bridges past, present, and future. The data are selected based on purposeful sampling with maximum variation sampling is used as the approach to show various perspectives about women’s issues in Hillary’s speeches.The research finds that Hillary considers it important to overcome women’s issues in all life spheres; education, economy, health, politics, and social that emerge due to the patriarchal system. It also finds that Hillary regards all issues in those spheres as interconnected thus they have to be dealt simultaneously. Hillary expects all society members, men and women, to be involved in overcoming those issues since women’s empowerment supports human advancement as well.Keywords: Hillary Clinton, women issues, women empowerment.